The influence of different leadership styles on the entrepreneurial process: A qualitative study - Juliana Baltazar; Mário Franco (Economies, 2023)
Leadership has become a complex, difficult subject with various facets for organisations, as it involves challenges regarding the best style for leaders to adopt. This study aims to analyse how the different leadership styles, presented throughout the various stages of the entrepreneurial process (discovery, application, implementation, and growth), can influence this type of process in the small and medium-sized enterprise (SME) context. To this end, qualitative research of an exploratory nature was undertaken, based on four Portuguese SMEs (case studies) from different sectors. Data were collected from interviews with leaders and followers in the four SMEs selected, as well as through documentary analysis. From the content analysis, the empirical evidence obtained leads to the conclusion that there is not just one leadership style followed by the SMEs analysed in the different stages of the entrepreneurial process. However, the transactional style of leadership was identified in two stages of that process: discovering the idea and implementing the idea. In the second stage of the entrepreneurial process, the application of the idea, a transformational style was identified, and at the final stage (growth), two leadership styles emerged: a participative style and a relational style. Therefore, the study contributes to advancing knowledge in the area by demonstrating how the style of leadership affects and influences not only the entrepreneurial process but also followers' behaviour and attitudes. In addition, this study suggests that sometimes entrepreneurship and leadership are used as interchangeable terms in the entrepreneurial process.
Keywords: 330; entrepreneurial process; leader; leadership; leadership styles; SME